Braided relations, entwined lives : the women of Charleston's urban slave society - Kennedy, Cynthia M. (Blacks in the diaspora., 2005)
This study of women in antebellum Charleston, South Carolina, looks at the roles of women in an urban slave society. Kennedy takes up issues of gender, race, condition (slave or free), and class and examines the ways each contributed to conveying and replicating power. Her study examines the lives of the women of Charleston and the variety of their attempts to negotiate the web of social relations that ensnared them.